A Review of Clinical Manifestation of COVID-19 Due to its Effect on the Vascular System - Siddik, Abu Bakar; Rahman, Tasnim; Rahman, Sajedur; Hossain, Mohammad D; Ferdousi, Mussammat Afsana; Tamanna, Kazi Nusrat; Shourav, Md Manjurul Islam; Turin, Fahmida Eskander; Sakibuzzaman, Md (Archives of Clinical and Biomedical Research, 2020)
Coronavirus disease 2019 (COVID-19) appears to raise significant public health concerns worldwide. COVID-19 can affect any organ, including the vascular system. Various clinical manifestations of COVID-19, including dermatological and renal manifestations, are likely to indicate vascular involvement. Vasculitis has been associated with COVID-19 as a potential pathological process in multiple cases but is not considered a primary pathology. The immune system produces a tremendous amount of pro-inflammatory cytokines due to COVID-19 infection. These pro-inflammatory cytokines cause endothelial dysfunction and thrombosis, which can lead to vasculitis. Further, COVID-19 can directly cause endothelial dysfunction by binding to angiotensin-converting enzyme 2 receptors of vascular endothelium. Ischemic changes and vessel thrombosis, which are common findings in vasculitis, were reported in histopathological examinations. Proper treatment and management of vasculitis associated with COVID-19 are our new concerns. This review article highlights some important clinical manifestations of COVID-19 infection due to its effect on the vascular system. The article also describes risk factors, pathogenesis, diagnosis, and possible treatment of this manifestation.